Practicality of E-Module Teaching Materials Integrated With Islamic Values On Global Warming Material at Senior High School - Agusminarti, Agusminarti; Sholihat, Neng; Nurbaiti, Desy; Ahda, Yuni (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
Islamic values in the subject matter of global warming symptoms for class XI at Senior high school. This research is a continuation of R&D research and development with the ADDIE model using 5 stages namely Analysis, Design, Development, Implementation, and Evaluation. The research instrument used was a practicality test questionnaire and student answer sheets on the e-module. there are 31 students and one educator have participated in this practicality test. The results of data analysis on the average value at the practicality test stage were carried out by educators and students. With the very practical category, the practicality analysis value of educators is 92.65 %, Very practical criteria for data analysis by students yielded 89.09 %. The results of the study concluded that the integrated e-module of Islamic values in the material on global warming symptoms that was developed was very practical to use in the learning process for class XI as an alternative teaching material in the learning processABSTRAK: Penelitian ini bertujuan untuk mengukur tingkat praktikalitas e-modul terintegrasi nilai-nilai islam pada materi gejala pemanasan global untuk kelas XI Sekolah Menegah Atas. Penelitian ini merupakan lanjutan penelitian dan pengembangan R&D dengan model ADDIE menggunakan 5 tahapan yaitu Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Instrumen penelitian yang digunakan berupa angket uji praktikalitas dan lembar jawaban peserta didik pada e-modul. terdapat 31 peserta didik dan satu pendidik telah berpartisipasi dalam pengujian kepraktisan ini. Hasil analisis data rata-rata nilai pada tahap uji praktikalitas dilakukan oleh pendidik dan peserta didik. Dengan katerogi sangat praktis diperoleh nilai analisis kepraktisan pendidik sebesar 92,65%, Kriteria sangat praktis analisis data oleh peserta didik menghasilkan sebesar 89,09%,. Hasil penelitian menyimpulkan bahwa e-modul terintegrasi nilai-nilai islam pada materi gejala pemanasan global yang dikembangkan sangat praktis digunakan dalam proses pembelajaran kelas XI sebagai bahan ajar alternative dalam proses pembelajaran.